1926
DOI: 10.1002/jlac.19264470114
|View full text |Cite
|
Sign up to set email alerts
|

Über eine neue Gewinnung von Pyrrol‐α‐aldehyden, sowie über stabile Tripyrrylmethane

Abstract: P i s c f i e r uttd B r n s t , vber eine n e w Getrinn7iny ~I S I I ' .Urnsetrung des Bromkorpers (V) mit Nott+wnucetat. 1 g Bromprodukt wird mit der 2-4 facbeu Menge Natriumacefat und Eisessig 1-2 Stunden am RiickfluBkiihler gekocht. Beim Abkiihlen scheidet sich das Acetat aus. Es wird aus Chloroform-Petrolather und aus Alkohol umkrystallisiert und ist dam analysenrein. Schmelzp. 114-1 15 O. Krystallform : Kndeln.7,4 ccin N (16O, 723 nun). 15'3 0,1090 g Subst.: 0,2958 g CO,, 0,0633 E; €I,O. -0,1764 g Subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1927
1927
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The Gattermann reaction, like halogenation, is capable of displacing carboxyl groups from the pyrrole ring (145), thus transforming a carboxylic acid to the corresponding aldehyde. Houben-Hoesch synthesis, in which either an aliphatic or aromatic nitrile is substituted for the hydrogen cyanide in the Gattermann reaction, serves to introduce keto groups in the pyrrole nucleus (139).…”
Section: O ^Etc•mentioning
confidence: 99%
“…The Gattermann reaction, like halogenation, is capable of displacing carboxyl groups from the pyrrole ring (145), thus transforming a carboxylic acid to the corresponding aldehyde. Houben-Hoesch synthesis, in which either an aliphatic or aromatic nitrile is substituted for the hydrogen cyanide in the Gattermann reaction, serves to introduce keto groups in the pyrrole nucleus (139).…”
Section: O ^Etc•mentioning
confidence: 99%
“…The other attempt to prepare 1 -phenyl-5-tetrazolylcarboxaldehyde was suggested by the work of Fischer and Ernst (7) who synthesized pyrrole aldehydes from the corresponding halomethyl compounds through conversion to the anilinomethyl derivatives followed by permanganate oxidation and hydrolysis of the resulting Schiff base. Thus l-phenyl-5-chloromethyltetrazole was reacted with aniline, using the method of Harvill and his co-workers (2) for the preparation of 5-N-substituted aminomethyltetrazoles, to give a 52% yield of 1-phenyl-5-anilinomethy ltetraz ole.…”
Section: C02etmentioning
confidence: 99%
“…However, it methods, the bromination of four 5-bromo-5'-had suggested that 5'-bromo~nethylpyrromethenes methylpyrromethenes under various conditions was would be favoured if 2-methylpyrroles were more followed by the 'Hmr signals of the CH2Br (or completely converted to 2-bromomethylpyrroles CH20Me) and bridge C H groups. The best results before condensing to pyrromethenes; thus 2-methylwere obtained in acetic acid after 45 min on the 5-tert-butoxycarbonylpyrroles were brominated to 5-bromo-5'-bro~nomethylpyrromethenes (12 2-carboxylic acids 2, for both a hydroxymethylpyrrole (13) and an ethoxymethylpyrromethene (66) had been converted into their bromomethyl derivatives by hydrogen bromide in acetic acid. This was not considered too promising because the acetoxymethyl groups might well be displaced by bromine before they were locked on as bromomethyl, a process requiring hydrogen bromide formed by the brominative displacement of the carboxyl group.…”
mentioning
confidence: 99%